Morinian Complexity and the Nursing Curriculum - Cecilia Rita RÉ (Universidad de Antioquia, 2020)
This scientific essay argues about the relevance of including Edgar Morin's complex thinking in the Nursing curriculum development. The curriculum determines the professional profile of Nursing teachers and future nurses, comprising the cognitive, moral, clinical, affective, research and trade union competencies necessary for professional survival. Complexity allows us to build new creative and critical curricula, with multidisciplinary thinking, connecting fragmented knowledge, defending one's own cultural identity, based on the Philosophy of care, and responding, in parallel, to the challenges of a politically imposed globalization, which is elective. The design of curricula that respond to the demands of the 21st century requires competent curriculum engineering able to triangulate Nursing, Education and Philosophy, given that citizens are been trained and not only specialized workers. The sciences of complexity humanize and complement the Cartesian and positivist scientific approach, influenced by the patriarchal paradigm. The curriculum changes its structure by including complex thinking references.